2018
DOI: 10.1007/s10897-018-0254-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement and Influence of Healthcare Providers, Family Members, and Other Mutation Carriers in the Cancer Risk Management Decision‐Making Process of BRCA1 and BRCA2 Mutation Carriers

Abstract: Deciding between increased cancer screening or prophylactic surgery and the timing of such procedures can be a difficult and complex process for women with BRCA mutations. There are gaps in our understanding of involvement of others in the decision-making process for women with BRCA mutations. This study evaluated the management decision-making process of women with BRCA mutations, focusing on the involvement of others. Grounded theory was used to analyze and code risk management decision-making information fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Men and individuals who did not have prior experience with genetic testing were also more likely to be ambivalent about their decision to participate. Consistent with findings by Puski and colleagues, participants who discussed their interest in genomic screening with a family member or friend were less likely to report decisional ambivalence 50. These data suggest that pretest genetic counselling resources and other decisional support tools might be prioritised for a subgroup of patients with specific risk factors related to the quality of their decision-making.…”
Section: Discussionsupporting
confidence: 80%
“…Men and individuals who did not have prior experience with genetic testing were also more likely to be ambivalent about their decision to participate. Consistent with findings by Puski and colleagues, participants who discussed their interest in genomic screening with a family member or friend were less likely to report decisional ambivalence 50. These data suggest that pretest genetic counselling resources and other decisional support tools might be prioritised for a subgroup of patients with specific risk factors related to the quality of their decision-making.…”
Section: Discussionsupporting
confidence: 80%
“…The distribution of MMAT-v2018 scores was generally high across study designs, with 22 out of 30 (73.3%) studies meeting 100% of quality criteria and eight records having 80% of quality criteria met (see Supplementary Table S1). All qualitative studies (n = 5) [14,56,[59][60][61] obtained the highest possible score, which was also achieved in 3 out of 7 (42.9%) quantitative non-randomized studies [62][63][64] and 13 out of 17 (76.5%) records adopting a quantitative descriptive method [55,[65][66][67][68][69][70][71][72][73][74][75][76]. One mixed-method study of the two included in this review (50%) also met 100% of the quality criteria [77].…”
Section: Description Of the Included Studies: The Mmat-v2018 Checklistmentioning
confidence: 89%
“…However, one study measured long-term adjustment of up to 24 months after receiving genetic testing results [72]. Five papers employed a qualitative research method conducted on pathogenic variant carriers and their family members [14,56,[59][60][61]. A summary of the characteristics of selected studies can be found in Table 1, while a more complete description of selected records can be consulted in Supplementary Table S2.…”
Section: Overview Of Characteristics Of Included Articlesmentioning
confidence: 99%
See 2 more Smart Citations